2022
DOI: 10.1155/2022/5416722
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Artificial Neural Network: Architecture, Types, and Forecasting Applications

Abstract: The artificial neural network reduces humanity and society’s burden to solve complex problems highly efficiently. Artificial neural networks resemble brain activities based on the acquired training samples used for various applications such as classification, regression, prediction, smart grid, natural language processing, image processing, medical diagnosis, and so on. This paper illustrates the different artificial neural network architectures, types, merits, demerits, and applications. Therefore, this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…ANN regression models are used in regression problems because they can solve complex non-linear relationships between input and output values by learning from a portion of the data and adapting accordingly [28]. The basic structure of an ANN model consists of an input layer, hidden layers, and an output layer [29].…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…ANN regression models are used in regression problems because they can solve complex non-linear relationships between input and output values by learning from a portion of the data and adapting accordingly [28]. The basic structure of an ANN model consists of an input layer, hidden layers, and an output layer [29].…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…In particular, a dramatic shift in the use of digital technologies has been identified that will affect all aspects of work and life. How this change plays out remains largely dependent on our reactions to emerging trends and how they will be shaped [16,93]. The energy sector is one industry that also stands to gain significantly from the deployment of Artificial Intelligence [94,95] following the pandemic crisis.…”
Section: The Impact Of the Covid-19 Pandemic On The Development Of Re...mentioning
confidence: 99%
“…The architectures of ANNs are inspired by the workability of human neural networks in the performance of some tasks [17]. They are constructed as connected neurons, which form the following layers: input, output, and hidden.…”
Section: Application Of Artificial Neural Network In the Analysis Of ...mentioning
confidence: 99%